Quality-Reliability Coupled Network Modeling and Importance Measure of Multi-Stage Manufacturing Systems via Network Controllability Analysis - Zhang, Ding; Pei, Yu; Liu, Qiang (Frontiers in Mechanical Engineering, 2022)
The fluctuation of product quality is closely related with the equipment’s degradation in multi-stage manufacturing systems. This paper proposes an importance measure approach for quality-reliability coupled network of multi-stage manufacturing system via network controllability analysis. The impact of component degradation will be transmitted, expanded and accumulated in multiple manufacturing stages, leading to quality flaws or even shutdowns of the entire system. An importance measure method via controllability analysis is provided by quantifying the impact of attacking the quality-reliability coupled network. By quantifying control ability of fault source node on key quality attribute node, the weakness that affect the processing accuracy of production line is identified. Case studies of real production lines are applied to verify the effectiveness, and comparative results shows the method can be applied to guide the accuracy reliability improvement of manufacturing systems.